Symptoms of Common Mental Disorders and occupational performance in the perception of young participants of pre-academic courses (Research, Society and Development, 2022)
Introdution: To join higher education, the young population is submitted to an exam designed to qualify the level of knowledge about the contents of basic education. Nevertheless, the preparation process for joining a university involves stressful events, that can become a risk period for the emergence of common mental disorders and for the satisfactory performance of everyday activities. Objective: This study aimed to identify symptoms of common mental disorders and the occupational performance from the students' perception in a preparatory course for ENEM in the city of Recife/PE. Methodology: Quantitative work and transversal approach, with data presented in the form of relative and absolute frequency. For the data collection, a socioeconomic, demographic, and occupational questionnaire, the Occupational Functioning Self-Assessment Scale and the Self Report Questionnaire, was used. Results and discussion: 38 students, aged between 17 and 24 years, participated in this study. Between the participants, 63.2% showed evidence for the common mental disorder, more apparent in women and related to the depressive-anxious mood, depressive thoughts, and reduced vital energy. Occupational performance concerning the practice of healthy habits and a structured routine also demonstrated damages. There are problems in self-management and organization of time, including sleep hygiene, lack of leisure, and sports activities that affect school performance. Conclusion: Hence, we alert to the need for the necessity of interventions to promote mental health with young people who are going through this stage, to ease adversity, and promote well-being, mental health, and quality of life.